2020
DOI: 10.3390/ijms21239115
|View full text |Cite
|
Sign up to set email alerts
|

Hedging against Neuropathic Pain: Role of Hedgehog Signaling in Pathological Nerve Healing

Abstract: The peripheral nervous system has important regenerative capacities that regulate and restore peripheral nerve homeostasis. Following peripheral nerve injury, the nerve undergoes a highly regulated degeneration and regeneration process called Wallerian degeneration, where numerous cell populations interact to allow proper nerve healing. Recent studies have evidenced the prominent role of morphogenetic Hedgehog signaling pathway and its main effectors, Sonic Hedgehog (SHH) and Desert Hedgehog (DHH) in the regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 102 publications
0
24
0
1
Order By: Relevance
“…In this study, GSEA results showed that CHRNA3 was enriched in neuroactive ligand-receptor interaction, ECM-receptor interaction, and IL-17 signaling pathway-related pathways, while CHRNB2 and CHRNB4 were related to ferroptosis, the toll-like receptor signaling pathway, the hedgehog signaling pathway, cell cycle, the mTOR signaling pathway, and inflammatory mediator regulation of TRP channels, respectively. Most of these signaling pathways mediate nerve injury and the continuation of NPP by participating in neurotoxicity [ 31 ], neural activity [ 32 ], inflammatory response [ 33 , 34 ], hyperalgesia [ 35 ], nerve healing [ 36 , 37 ], microglia polarization [ 38 ], and oxidative stress [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, GSEA results showed that CHRNA3 was enriched in neuroactive ligand-receptor interaction, ECM-receptor interaction, and IL-17 signaling pathway-related pathways, while CHRNB2 and CHRNB4 were related to ferroptosis, the toll-like receptor signaling pathway, the hedgehog signaling pathway, cell cycle, the mTOR signaling pathway, and inflammatory mediator regulation of TRP channels, respectively. Most of these signaling pathways mediate nerve injury and the continuation of NPP by participating in neurotoxicity [ 31 ], neural activity [ 32 ], inflammatory response [ 33 , 34 ], hyperalgesia [ 35 ], nerve healing [ 36 , 37 ], microglia polarization [ 38 ], and oxidative stress [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, GSEA results showed that CHRNA3 was enriched in neuroactive ligandreceptor interaction, ECM-receptor interaction, and IL-17 signaling pathway-related pathways, while CHRNB2 and CHRNB4 were related to ferroptosis, the toll-like receptor signaling pathway, the hedgehog signaling pathway, cell cycle, the mTOR signaling pathway, and inflammatory mediator regulation of TRP channels, respectively. Most of these signaling pathways mediate nerve injury and the continuation of NPP by participating in neurotoxicity [31], neural activity [32], inflammatory response [33,34], hyperalgesia [35], nerve healing [36,37], microglia polarization [38], and oxidative stress [39]. e nicotine and nicotinic acetylcholine receptors (NAChRs) subtype, by a variety of subunits of combinatorial synthesis channel receptor complexes, its structure, and function in the nervous system of diversity, had been found to enhance the presynaptic neurotransmitter and release and affect the excitability of neurons, and when its function declines, it would cause the nervous system dysfunction [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The most recently identified protein that appears to function in this way is Sonic hedgehog (Shh) (reviewed in Moreau and Boucher, 2020 ). Shh and Gli1, one of the downstream effectors of Shh signaling, are up-regulated in repair cells after injury, while Shh is also expressed in DRG neurons (Hashimoto et al, 2008 ; Arthur-Farraj et al, 2012 ; Martinez et al, 2015 ; Yamada et al, 2018 ).…”
Section: The Pharmacology Of Regeneration: Hijacking the Autocrine Lo...mentioning
confidence: 99%
“…The effectors of these pathways Sonic Hedgehog and Desert Hedgehog are involved in the nerve regeneration. Sonic Hedgehog initiates the neovascularization in the vicinity of the injured nerve to facilitate regeneration in diabetic rats [ 75 ]. A recent study demonstrated that the upregulation of microRNAs, miR-9 and miR-29a, leads to diabetic neuropathy and the painful symptoms.…”
Section: Metabolic Pathways Of Painful Diabetic Neuropathy (Pdn) and Potential Therapeutic Agentsmentioning
confidence: 99%